Quantitative and qualitative detection of metabolic compounds in the seeds of cress plant (Lepidium sativum.L) using chromatography tech-nique - Ismael, Inas A.; Khorsheed, Ayad C. (Journal of Kerbala for Agricultural Sciences, 2021)
The natural compounds are considered one of the important natural source for giving effective and medicinal compounds, especially in the varions aspects due to the nature of their composition, safety of use and of access to their sources in nature. One of these plants is Lepidium sativum that grown in Iraq. In this research, volatile oils were separated from the seeds and calculating their concentration in ratio and also identification with GLC- technique which included. (alpha-pinene, Linalool, comphour, camphere, limonene, terpene and Myrcene). Also chromatographic analysis showed that the seeds contain of many of many of fatty acid compounds which included: (palmitic acid, oleic acid, Linoleic acid, stearic acid, Eicosenoic acid, linolinic acid, butyric acid and undeconaic acid).